Physical activity during a prolonged congested period in a top-class European football team - Djaoui, L.; Wong, D. P.; Pialoux, V.; Hautier, C.; da Silva, C. D.; Chamari, K.; Dellal, A. (Asian Journal of Sports Medicine, 2014)
Purpose: The aim of the present study was to examine the variation in physical activity of elite soccer players within successive prolonged periods of fixture congestion over 5 months of competition during the competitive season 2011-2012.